Results of the pToWin study: using the pCONUS device for the treatment of wide-neck intracranial aneurysms - Aguilar Pérez, Marta; Henkes, Hans; Kurre, Wiebke; Bleise, Carlos; Lylyk, Pedro Nicolás; Lundquist, Javier; Turjman, Francis; Alhazmi, Hanan; Loehr, Christian; Felber, Stephan; Deutschmann, Hannes; Lowens, Stephan; et al. (Journal of Clinical Medicine, 2022)
Coil embolization has become a well-established option for the treatment of intracranial aneurysms. Yet, wide-neck bifurcation aneurysms (WNBAs) remain a challenge. The pCONUS is the first generation of a stent-like implant for the bridging of WNBAs to enable coiling. The pToWin study was a prospective, single-arm, multicenter study conducted to analyze the safety and efficacy of the pCONUS in the treatment of WNBAs. The primary effectiveness endpoint was the rate of adequate occlusion of the aneurysm at 3-6 and 7-12 months. The primary safety endpoint was the occurrence of major ipsilateral stroke or neurological death during the follow-up. A total of 115 patients were included. Aneurysm locations were the middle cerebral artery in 52 (45.2%), the anterior communicating artery in 35 (30.4%), the basilar artery in 23 (20%), the internal carotid artery terminus in three (2.6%), and the pericallosal artery in two (1.7%) patients. Treatment was successfully performed in all but one patient. The morbi-mortality rate was 1.9% and 2.3% at 3-6 and 7-12 months, respectively. Of the aneurysms, 75.0% and 65.6% showed adequate occlusion at 3-6 and 7-12 months, respectively. pCONUS offers a safe and reasonably effective treatment of WNBAs, demonstrated by acceptable adequate aneurysm occlusion and low rates of adverse neurologic events.
Gesehen am 23.03.2022